PERLINDUNGAN HUKUM BAGI INVESTOR TERHADAP PERJANJIAN PENYALURAN FASILITAS PINJAMAN MELALUI CROWDFUNDING YANG WANPRESTASI - Olga Sekar Anggun Hamidah; Wiwin Yulianingsih (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2022)
This research is a normative juridical legal research using a qualitative approach. The purpose of this study is to analyze and understand the legal protection provided to investors in the loan facility distribution agreement on the Tanifund platform. The agreement itself, in particular the clauses agreed upon by the parties, contains the legal protection that the parties provide. There is also outside the agreement, that is, the provisions of existing laws and regulations. Legal protection is essential to ensure that one's legal rights are upheld as well as create legal certainty, legal expediency, and justice for the parties. The results of this study can be concluded that the agreement agreed upon by the loan-based crowdfunding platform gives rise to a legal relationship. A legal relationship is one of the relationships that produces legal consequences guaranteed by the law as well as the Law. Any legal action on a loan-based crowdfunding site should be protected by law, especially if there is disagreement between the parties. Legal protection is necessary to provide solutions and clarity on the resolution of existing or potential disputes after an agreement has been made, because peaceful forums or through deliberations cannot be guaranteed to address existing problems.